Language Acquisition of Children Aged 2.0–2.6 Years in Lapolea Village: A Psycholinguistic Study: Pemerolehan Bahasa pada Anak Usia 2,0–2,6 Tahun di Desa Lapolea: Kajian Psikolinguistik - Asni Sasnita; Sulfiah; La Ode Adili (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2026)
This study aims to describe the language acquisition of children aged 2.0–2.6 years in Lapolea Village from a psycholinguistic perspective, focusing on phonological, morphological, phrasal, sentential, and semantic development. The study employed a descriptive qualitative design with a case study approach involving two children: Azahra Riskiani, aged 2 years and 6 months, and Muhamad Rizki Azmi Rahman, aged 2 years and 5 months. The data consisted of the children’s natural utterances collected through observation, listening, note-taking, audio recording, and contextual interviews with parents over a two-week period. Data were analyzed through transcription, reduction, coding based on linguistic categories, data presentation, interpretation, and verification through parental confirmation. The findings indicate that both children had acquired the basic vowels /a/, /i/, /u/, /e/, and /o/, most consonant sounds, free morphemes, nominal phrases, verbal phrases, adjectival phrases, prepositional phrases, as well as declarative, imperative, interrogative, and simple negative sentence forms. Azahra demonstrated relatively longer and more complex utterances, whereas Rizki predominantly used single words or short phrases; however, the intended meanings of his utterances remained comprehensible. Semantically, both children were able to adjust their utterances according to contextual meanings. The study concludes that the language acquisition of both children is within the expected developmental range for their age, although individual differences are evident and influenced by articulatory maturity and the intensity of social interaction. This research contributes empirical data on child language acquisition in a rural setting, particularly in Lapolea Village, thereby enriching psycholinguistic studies of Indonesian children and providing useful references for parents, early childhood educators, and researchers in child language development.